Minimally invasive image‐guided cochlear implantation surgery: First report of clinical implementation. (6th January 2014) - Labadie, Robert F.; Balachandran, Ramya; Noble, Jack H.; Blachon, Grégoire S.; Mitchell, Jason E.; Reda, Fitsum A.; Dawant, Benoit M.; Fitzpatrick, J. Michael
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Minimally invasive image‐guided approach to cochlear implantation (CI) involves drilling a narrow, linear tunnel to the cochlea. Reported herein is the first clinical implementation of this approach. Study Design Prospective cohort study. Methods On preoperative computed tomography (CT), a safe linear trajectory through the facial recess targeting the scala tympani was planned. Intraoperatively, fiducial markers were bone‐implanted, a second CT was acquired, and the trajectory was transferred from preoperative to intraoperative CT. A customized microstereotactic frame was rapidly designed and constructed to constrain a surgical drill along the desired trajectory. Following sterilization, the frame was employed to drill the tunnel to the middle ear. After lifting a tympanomeatal flap and performing a cochleostomy, the electrode array was threaded through the drilled tunnel and into the cochlea. Results Eight of nine patients were successfully implanted using the proposed approach with six insertions completely within the scala tympani. Traditional mastoidectomy was performed on one patient following difficulty threading the electrode array via the narrow tunnel. Other difficulties encountered included use of the backup implant when an electrode was dislodged during threading via the tunnel, tip fold‐over, and facial nerve paresis (House‐Brackmann II/VI at 12 months) secondary to heat during drilling. The average time of intervention was 182 ± 36 minutes. Conclusions Minimally invasive image‐guided CI is clinically achievable. Further clinical study is necessary to address technological difficulties during drilling and insertion, and to assess potential benefits including decreased time of intervention, standardization of surgical intervention, and decreased tissue dissection potentially leading to shorter recovery and earlier implant activation. Level of Evidence 4. Laryngoscope, 124:1915–1922, 2014